Decoupling microbial iron reduction from anoxic microsite formation in oxic sediments: a microscale investigation through microfluidic models - Ceriotti, Giulia; Bosco-Santos, Alice; Borisov, Sergey M.; Berg, Jasmine S. (Frontiers in Microbiology, 2025)
Iron (Fe) reduction is one of the oldest microbial processes on Earth. After the atmosphere and ocean became oxygenated, this anaerobic process was relegated to niche anoxic environments. However, evidence of Fe reduction in oxic, partially saturated subsurface systems, such as soils and vadose zones, has been reported, with the common explanation being the formation of anoxic microsites that remain undetected by bulk measurements. To explore how microscale oxygen concentrations regulate microbial Fe reduction, we cultivated a facultative Fe-reducing bacterium using a microfluidic setup integrated with transparent planar oxygen sensors. Contrary to expectations, Fe reduction occurred under fully oxic conditions, without the formation of anoxic microsites. Our results suggest that microbially mediated Fe-reduction could be more widespread in oxic subsurface environments than previously assumed. Moreover, our mathematical modeling of oxygen dynamics around biomass-rich layers revealed that the onset of anoxia is mainly controlled by biomass spatial organization rather than the conventionally used water saturation index. This opens a new perspective on the proxies needed to predict anoxic microsite formation and Fe(III) reduction occurrence.